Robust Portfolio Rules and Asset Pricing - Maenhout, Pascal J. (Review of Financial Studies, 2004)
I present a new approach to the dynamic portfolio and consumption problem of an investor who worries about model uncertainty (in addition to market risk) and seeks robust decisions along the lines of Anderson, Hansen, and Sargent (2002). In accordance with max-min expected utility, a robust investor insures against some endogenous worst case. I first show that robustness dramatically decreases the demand for equities and is observationally equivalent to recursive preferences when removing wealth effects. Unlike standard recursive preferences, however, robustness leads to environment-specific “effective” risk aversion. As an extension, I present a closed-form solution for the portfolio problem of a robust Duffie-Epstein-Zin investor. Finally, robustness increases the equilibrium equity premium and lowers the risk-free rate. Reasonable parameters generate a 4% to 6% equity premium.